Evaluation of Sun and Oven-Dried Broiler Offal Meal as Replacement for Fishmeal in Broiler and Layer Rations - Isika, M.A.; Eneji, C.A.; Agiang, E.A. (International Journal of Poultry Science, 2006)
Two feeding trails were conducted to determine the replacement value of broiler offal meal for fishmeal, if it is processed by oven-drying in addition to sun-drying. Fishmeal was replaced at the rate of 0%, 50%, and 100% with sun and oven dried offal meal (SOBOM) in broiler and layer diets each. While the broiler rations had 230g/kg crude protein and 2906 Kcal/kg of metabolizable energy, the layer diets had 175g/kg crude protein and 2700 Kcal/kg of metabolizable energy in a completely randomized designed experiment. The three treatments were replicated thrice in experiment I using 315 Anak 2000 broiler chicks, while experiment II had 360, 32-week Lohmann brown layers. The birds were randomly assigned to three treatments with three replicates in each group. The broiler results showed that, the body weight and feed conversion ratio were significantly (P< 0.05) superior in birds fed with fishmeal than those on SOBOM diets. However, in the layers; hen-day production, egg-size, shell thickness, feed intake and feed conversion ratio were statistically similar in all groups. The study showed that broiler offal meal was inferior to fishmeal in broiler performance, but was comparable even at 100% replacement level for layers performance.